Entrepreneurial Orientation and Business Performance: An Assessment of Start-up Companies - Dr. Jagadish Brahma Goulap (International Journal of Engineering and Management Research, 2020)
The purpose of the present research is to analyse from the core constructive influence of entrepreneurial orientation (EO) (risk taking, innovativeness, and pro-activeness) on the business performance (BP) of start - up enterprises. Various related literature aspects discussed for to embrace entrepreneurial orientation to increase business performance. Profitability index, size, age, return on sales, technological advancement, profit and sales among others used to relate EO with BP. Linear regression models, descriptive statistics, Pearson’s correlation, Cronbach's Alpha for reliability test etc., among many used to relate statistically EO with BP. Sample of 53 start-up firms from Addis Ababa, Ethiopia, chosen for data interpretation. It is found out that there is a positive relationship exists between Entrepreneurial Orientation (EO) and Business performance (BP). This study wants to create awareness and knowledge among startup entrepreneurs to adopt entrepreneurship. In the global competitive and dynamic environment to outperform rivals, start-up companies expected to become entrepreneurial to meet long-term goals of superior performance by discovering new and better entrepreneurial opportunities. To focus more on entrepreneurial opportunity, attention be given on knowledge creation and understanding towards EO process, practices, and decisions making, which will help to have more competitive advantage for higher performances and as a whole develop countries economy.